2011
DOI: 10.2136/vzj2010.0061
|View full text |Cite
|
Sign up to set email alerts
|

Vadose Zone Water Pressure Variation during Infiltration Events

Abstract: Measurements of vadose zone water pressure using custom‐made tensiometers provided insight into the dynamics of rainfall‐induced infiltration events in a 22‐m‐thick sandy formation. The tensiometers, based on vadose zone sampling ports, were assembled in a vadose zone monitoring system that allowed in situ, real‐time measurements of the temporal variation in vadose zone water content and pore water pressure. Results revealed the critical relationship between temporal variations in vadose zone water content and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It is highly possible that desiccation cracks from the margins create a network of horizontal connectivity under the pond, as has been observed in large‐scale lysimeter experiments and modeled by numerical models (Chertkov, ; Greve et al ., ). It is suggested that the formation of desiccation cracks around and under the manure pond can accelerate the aeration of the unsaturated vadose zone, via a variety of mechanisms: (1) thermal‐induced air convection in the cracks (Nachshon et al ., ), (2) barometric pressure fluctuations in the vadose zone caused by daily atmospheric pressure fluctuations (Rimon et al ., ), and (3) wind gusts (Auer et al ., ; Neeper, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly possible that desiccation cracks from the margins create a network of horizontal connectivity under the pond, as has been observed in large‐scale lysimeter experiments and modeled by numerical models (Chertkov, ; Greve et al ., ). It is suggested that the formation of desiccation cracks around and under the manure pond can accelerate the aeration of the unsaturated vadose zone, via a variety of mechanisms: (1) thermal‐induced air convection in the cracks (Nachshon et al ., ), (2) barometric pressure fluctuations in the vadose zone caused by daily atmospheric pressure fluctuations (Rimon et al ., ), and (3) wind gusts (Auer et al ., ; Neeper, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to characterize flow and transport processes in the vadose zone was recently improved following the development of a vadose zone monitoring system (VMS) that provides realtime, in situ information on the hydraulic and chemical state of the percolating water across the entire vadose zone. Up to now, the VMS has been implemented in a variety of hydrological setups, including (1) flood water percolation (Dahan et al, , 2008Amiaz et al, 2011), (2) rain water percolation through thick unsaturated sand and clay formations (Rimon et al, 2007(Rimon et al, , 2011bBaram et al, 2012a), and (3) solute transport in the vadose zone (Dahan et al, 2009;Rimon et al, 2011a;Baram et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…However, natural percolation events driven by natural wetting and drying cycles might occur on a scale of hours to days. Moreover, recent studies have demonstrated that the bulk chemical and isotopic characteristics of sediment samples often do not represent the properties of the mobile water due to macro‐scale preferential flow (McMahon et al, 2006; Gurdak et al, 2008; Kurtzman and Scanlon, 2011; Baram et al, 2012) and pore‐scale preferential flow (Rimon et al, 2011).…”
mentioning
confidence: 99%